A biodegradable antibacterial magnesium alloy staple and preparation method thereof

By applying Mg-xCa-yM silk material with biopolysaccharides and black phosphorus on the surface of magnesium alloy staples, the problems of non-degradable, poor acid and alkali resistance and lack of antibacterial and anti-inflammatory functions of existing staple materials are solved. The efficient preparation and safe healing of biodegradable antibacterial magnesium alloy anastomosis staples are achieved.

CN117018300BActive Publication Date: 2025-01-03YANSHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310704919.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2025-01-03
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

The existing anastomosis staple materials have problems such as non-degradable, poor acid and alkali resistance, lack of antibacterial and anti-inflammatory functions, and imperfect drug loading technology, which affects wound healing and safety.

Method used

Using biodegradable antibacterial magnesium alloy staples, the corrosion resistance of magnesium alloy is improved through alloying means, and the surface is coated with a mixed coating of Mg-xCa-yM silk material, biopolysaccharides and their derivatives and black phosphorus. , regulates degradability and antibacterial properties, and uses elements such as K, Zn, Ag, Mn to improve the biocompatibility and heat resistance of the materials.

Benefits of technology

The controllable degradability and antibacterial properties of magnesium alloy anastomosis are realized, and the degradation products are non-toxic, which enhances the acid and alkali resistance and antibacterial properties of the material, simplifies the preparation process, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117018300B_ABST
    Figure CN117018300B_ABST
Patent Text Reader

Abstract

The present application relates to the field of medical bioalloys, and more specifically, it relates to a biodegradable antibacterial magnesium alloy staple and a preparation method thereof. The degradable antibacterial magnesium alloy staple comprises a Mg‑xCa‑yM wire, a biopolysaccharide and its derivatives, and a black phosphorus mixed coating, wherein M in the Mg‑xCa‑yM wire is K, Zn, Ag, Mn and rare earth elements, the mass fraction of x is 0.1%‑15%, and the mass fraction of y is 0.01%‑6%. The degradability can be regulated, and the degradation products are harmless. The coating material is easy to obtain and modify, and has excellent antibacterial and acid and alkali resistance. The preparation process of the present application is simple, the production cycle is short, and it is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of medical bioalloys, and more specifically, to a biodegradable antibacterial magnesium alloy staple and a preparation method thereof. Background Art

[0002] In recent years, the traditional method of manual suturing of wounds with needles and threads has gradually been replaced by stapler suturing. The use of staplers greatly shortens the operation time, reduces the exposure time of the wound, is easy to operate, and reduces the possibility of side effects and surgical complications. However, the staplers commonly used today are mostly made of inert materials such as titanium alloys, which are not biodegradable. They exist in the human body as foreign bodies for a long time after surgery, which not only affects medical imaging observations, but also increases the possibility of inflammation and even causes tissue hyperplasia in the wound. In addition, the physiological environment in the human body is complex, and staples can be used in different parts such as the intestines and stomach. There are huge differences in the acidity and alkalinity of the use environment, so the ideal stapler needs to provide the necessary acid and alkali resistance in the early postoperative period to avoid its premature failure and degradation.

[0003] Since magnesium alloys have a density and elastic modulus that are extremely close to those of human cortical bones, as well as biodegradability and good biocompatibility, technicians in this field have proposed using staplers made of magnesium alloys to replace titanium alloys. Magnesium alloys have many advantages, such as good mechanical properties. After being implanted in the human body, they can greatly reduce the patient's discomfort and facilitate the patient's recovery; good biocompatibility. Magnesium is one of the most abundant trace elements in the human body and is one of the participants in human metabolic activities; it is biodegradable and can gradually degrade in the human body. After degradation, it can be directly absorbed by the human body or excreted from the body. However, magnesium alloys have poor corrosion resistance and a fast degradation rate. In addition, gastric staplers are often used in acidic environments, which makes it difficult for them to support the wound until it recovers and then completely degrades, resulting in secondary rupture of the wound.

[0004] The published Chinese invention patent "A biodegradable Mg-Zn-Ca-M stapler material and its preparation method" (publication number: CN109972007A) uses mostly non-toxic elements in the human body, which solves the problem that titanium alloy staplers cannot be degraded. However, it does not take into account the corrosion resistance of the stapler in the acidic environment of the stomach, and there may be a risk of premature degradation and failure.

[0005] The published Chinese invention patent "Absorbable stapler for stapler" (publication number: CN201210424102.7) consists of a stapler body made of medical degradable magnesium alloy wire, a degradable bioceramic film bottom layer attached to the surface of the magnesium alloy wire, and a degradable polymer surface layer for sealing. It has better corrosion resistance and can be completely degraded and absorbed in the body environment. It can also provide acid or alkali resistance in the early stage. However, when using staplers, bacterial infection or inflammation may occur during the wound recovery process. Therefore, if the staplers themselves have antibacterial properties, the probability of bacterial infection and inflammation can be reduced, thereby accelerating the healing of the wound.

[0006] The Chinese invention patent that has been published, "A gastrointestinal anastomotic staple with a degradable drug film layer and its preparation method" (publication number: CN202021461075.7), is a staple made of magnesium alloy with two parallel upper and lower surfaces. The drug-loaded film layer is composed of a porous oxide film containing drug molecules, which can effectively reduce the risk of broken staples during preparation and use, and can inhibit the proliferation of tumor cells that may remain and promote the healing of the anastomosis. However, the current drug loading on the metal layer has poor binding force and it is difficult to maintain the activity of the drug.

[0007] In summary, the main disadvantages of current staplers are:

[0008] (1) Titanium alloys and other materials cannot be degraded in vivo;

[0009] (2) Failure to provide the necessary acid and alkali resistance;

[0010] (3) Lack of antibacterial and anti-inflammatory functions;

[0011] (4) Drug loading technology needs to be improved. Summary of the invention

[0012] The present invention provides a biodegradable antibacterial magnesium alloy staple and a preparation method thereof, wherein the degradability can be controlled and the degradation products are harmless.

[0013] In a first aspect, the present disclosure provides a biodegradable antibacterial magnesium alloy staple, which comprises a Mg-xCa-yM wire, biopolysaccharides and their derivatives, and a black phosphorus mixed coating, wherein M in the Mg-xCa-yM wire is K, Zn, Ag, Mn and rare earth elements, the mass fraction of x is 0.1%-15%, and the mass fraction of y is 0.01%-6%.

[0014] The corrosion resistance of magnesium alloy is improved by alloying, and the degradation is regulated by adjusting the ratio. The selected elements are harmless to the human body, so the degradation products have no toxic side effects on the human body. The addition of calcium increases the hydrogen evolution overpotential and reduces the anode reaction rate; the addition of manganese reduces the micro-battery effect of impurity iron as the cathode and improves the toughness of the alloy; the addition of rare earth elements improves the heat resistance of magnesium alloy and also refines the grains; K, Ag, and Zn are essential elements in the human body and can be absorbed by the human body as nutrients after degradation.

[0015] Preferably, M in the Mg-xCa-yM wire is one or two of the rare earth elements K, Zn, Ag, Mn, Ge, Nd, Gd, Dy, and Y.

[0016] In a second aspect, the present disclosure provides a method for preparing a biodegradable antibacterial magnesium alloy staple, comprising the following steps:

[0017] S1. Weigh the required raw materials of metal calcium, metal manganese, metal yttrium and metal magnesium, melt the metal magnesium block in a resistance furnace in a mixed atmosphere of SF6 and CO2, heat it to 650-780°C, and keep it warm for 1.5-3h to obtain magnesium liquid, preheat the metal calcium, the metal manganese and the metal yttrium, and then slowly add them into the magnesium liquid in batches, refine the mixed magnesium liquid, put it back into the resistance furnace for heating after refining, pour it, and obtain a magnesium ingot after cooling, anneal the magnesium ingot and then perform hot drawing to obtain a magnesium alloy wire;

[0018] S2, immersing the prepared magnesium alloy wire into a silane coupling agent for functionalization;

[0019] S3, weighing the required black phosphorus, grinding it into powder, dispersing it in N-methylpyrrolidone, ultrasonicating it in an ice bath for 10 hours, and then high-speed centrifuging it to obtain a black phosphorus nanosheet solution, weighing the required polysaccharides and their derivatives, dissolving them in an organic solution, stirring them at room temperature for 2 hours to obtain a uniform polysaccharide solution, and stirring and mixing the black phosphorus supernatant and the polysaccharide solution at 36-38° C. for 12-24 hours to obtain a mixed coating solution of black phosphorus, polysaccharides and their derivatives;

[0020] S4. Coating the coating solution prepared in S3 on the surface of the functionalized wire prepared in S2 by dipping, spraying or hydrothermal synthesis, and curing under ultraviolet light for 10-14 hours to obtain a biodegradable antibacterial magnesium alloy staple with a coating thickness of 0.1-200 μm.

[0021] The coating material is easy to obtain and modify, and polysaccharides and their derivatives have excellent antibacterial properties, which can promote wound recovery and reduce inflammatory responses; the coating improves the acid and alkali resistance of the alloy material, and can be applied to a variety of organs in view of the complex pH environment in the human body; the coating thickness can be regulated according to the length of the preparation time, thereby controlling the degradation rate; the preparation process of the present application does not require high temperature and high pressure, the preparation method is simple, the cost is low, the production cycle is short, and it is suitable for large-scale production.

[0022] Preferably, in S1, after refining, the product is put back into the resistance furnace, heated to 800-1100° C., and kept warm for 30-60 minutes.

[0023] Preferably, in S1, the magnesium ingot is annealed at 400-800°C, and then hot drawn at 200-400°C for multiple passes, and the magnesium alloy wire is drawn to 0.2-0.6 mm.

[0024] Preferably, in S1, the purity of the raw materials is 99.99%, and in the mixed atmosphere of SF6 and CO2, the volume ratio of SF6 to CO2 is 90-100:1.

[0025] Preferably, in S3, the concentration of the black phosphorus nanosheet solution is 0.1-5 g / ml, the molecular weight of the biological polysaccharides and their derivatives is 2000-50000 Da, the concentration of the uniform polysaccharide solution is 0.5-10 g / ml, and the mass ratio of the black phosphorus to the polysaccharides and their derivatives in the mixed coating solution is 0.005:1-10:1.

[0026] Preferably, in S3, the biopolysaccharide and its derivatives are one or more of alginate, chitosan, chitosan polyammonium salt, dandelion polysaccharide, dextran, astragalus polysaccharide, polygonatum polysaccharide, rehmannia polysaccharide, chitin, cellulose, hyaluronic acid, chondroitin sulfate, and heparin.

[0027] Preferably, in S3, the organic solvent is one of N,N-dimethylformamide, tetrahydrofuran, ethanol, acetone, isopropanol, dimethyl sulfoxide, N-methylpyrrolidone, pyridine and acetonitrile.

[0028] Preferably, in S4, the coating coating method is dipping, spraying or hydrothermal synthesis, the dipping time is 5-30 min, the spraying carrier gas is one of nitrogen and argon, the gas pressure is 0.5-0.9 MPa, the spraying distance is 10-50 mm, the nozzle movement speed is 10-30 mm / s, the hydrothermal synthesis temperature is 120-200°C, and the time is 12-24 h.

[0029] In summary, this application has the following beneficial effects:

[0030] 1. Since the degradability in this application can be regulated, the degradation products are harmless and have good corrosion resistance;

[0031] 2. The coating material in this application is easy to obtain and modify, and has excellent antibacterial and acid and alkali resistance;

[0032] 3. The preparation process of this application is simple, the production cycle is short, and it is suitable for large-scale production.

[0033] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] 1. Figure 1 is a metallographic diagram of the biodegradable magnesium-calcium-manganese-yttrium alloy in Example 1 of the present application;

[0035] 2. Figure 2 This is the polarization curve diagram of magnesium, calcium and potassium after coating in Example 2 of the present application. DETAILED DESCRIPTION

[0036] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0037] Example

[0038] Example 1

[0039] A method for preparing a biodegradable antibacterial magnesium alloy staple comprises the following steps:

[0040] S1. Weigh the required raw materials of 1g of metallic calcium, 0.1g of metallic manganese, 0.1g of yttrium and 998.8g of metallic magnesium, all of which have a purity of 99.99%; melt the magnesium block in a resistance furnace in a mixed atmosphere of SF6 and CO2 (wherein SF6 accounts for 1 vol.%), heat it to 780°C, keep it warm for 1.5h, preheat the metallic calcium, manganese and yttrium and slowly add them into the magnesium liquid in batches; refine the mixed magnesium liquid; after refining, put it back into the resistance furnace, heat it to 800°C, keep it warm for 60min, pour it, and after cooling, obtain a magnesium ingot Mg-0.1Ca-0.01Mn-0.01Y; anneal the magnesium ingot at 400°C, and then perform multi-pass hot drawing at 200°C, draw it to 0.6mm, obtain a magnesium alloy wire, rinse it with deionized water and dry it;

[0041] S2, immersing the prepared magnesium alloy wire into a silane coupling agent for functionalization;

[0042] S3. Weigh 10g of black phosphorus, grind it into powder, disperse it in 100ml of N-methylpyrrolidone, ultrasonicate it in an ice bath for 10h, and then centrifuge it at high speed to obtain a black phosphorus solution with a concentration of 0.1g / ml; weigh 10g of chitosan, dissolve it in 20ml of acetone, stir it at room temperature for 2h, and obtain a uniform solution with a concentration of 0.5g / ml; stir and mix the black phosphorus solution and the chitosan solution at 36°C for 24h to obtain a mixed coating solution with a mass ratio of black phosphorus to chitosan of 0.005:1;

[0043] S4. Through the hydrothermal synthesis method, the wire obtained in S1 and the coating solution obtained in S2 are placed in a polytetrafluoroethylene reactor, synthesized at 200° C. for 12 hours, and cured under ultraviolet light for 10 hours to obtain a biodegradable antibacterial magnesium alloy anastomotic staple.

[0044] like Figure 1 This is the metallographic diagram of the alloy after smelting. Metallography refers to the chemical composition of the metal or alloy and the physical and chemical states of various components inside the alloy. Metallographic structure reflects the specific form of the metal phase. The internal structure of metal materials can only be observed under a microscope. The internal structure seen under a microscope is called microstructure or metallographic structure. The grain size of the alloy is about 200μm, which is much smaller than the grain size of cast pure magnesium (~1cm), indicating that the magnesium-calcium-manganese-yttrium alloy obtained in Example 1 has smaller grains. Microalloying can refine the grain size of pure magnesium, thereby improving the corrosion resistance of the magnesium alloy.

[0045] Example 2

[0046] A method for preparing a biodegradable antibacterial magnesium alloy staple comprises the following steps:

[0047] S1. Weigh 30g of metallic calcium, 0.5g of metallic potassium and 969.5g of metallic magnesium, all with a purity of 99.99%; melt the magnesium block in a resistance furnace in a mixed atmosphere of SF6 and CO2 (wherein SF6 accounts for 1 vol.%), heat it to 700°C, keep it warm for 2h, preheat the metallic calcium and other raw materials and slowly add them into the magnesium liquid in batches; refine the mixed magnesium liquid; after refining, put it back into the resistance furnace, heat it to 900°C, keep it warm for 40min, pour it, and obtain a magnesium ingot Mg-3Ca-0.05K after cooling; anneal the magnesium ingot at 500°C, and then perform multi-pass hot drawing at 400°C, draw it to 0.4mm, obtain a magnesium alloy wire, rinse it with deionized water and dry it;

[0048] S2, immersing the prepared magnesium alloy wire into a silane coupling agent for functionalization;

[0049] S3, weigh 10g of black phosphorus, grind it into powder, disperse it in 10ml of N-methylpyrrolidone, ultrasonicate it in an ice bath for 10h, and then centrifuge it at high speed to obtain a black phosphorus solution with a concentration of 1g / ml; weigh 10g of alginate, dissolve it in 5ml of dimethyl sulfoxide, stir it at room temperature for 2h, and obtain a uniform solution with a concentration of 2g / ml; stir and mix the black phosphorus solution and the alginate solution at 37°C for 12h to obtain a mixed coating solution with a mass ratio of black phosphorus to alginate of 1:1;

[0050] S3. Spraying was performed 20 mm above the wire obtained in S1 by spraying method. Argon was selected as carrier gas with a pressure of 0.6 MPa and a nozzle movement speed of 20 mm / s. The coating solution obtained in S2 was applied and cured under ultraviolet light for 12 h to obtain a biodegradable antibacterial magnesium alloy staple.

[0051] Polarization curves are of great significance in the study of metal corrosion. Their shape and changing patterns reflect the kinetic characteristics of the electrochemical corrosion process. From them, we can obtain the corrosion rate, corrosion mechanism, analysis of corrosion control factors and the main parameters of electrochemical protection. The polarization curve is a relationship curve between the polarization potential of the anodic reaction and the cathodic reaction of the corroded metal electrode and the logarithm of the polarization current density. Figure 2 This is the polarization curve of Mg-3Ca-0.05K. As can be seen from the figure, its corrosion potential is about -1.49mV. It is the potential measured when the metal reaches a stable corrosion state without external current. It indicates the difficulty of corrosion. The smaller the corrosion potential, the more difficult it is to corrode. Secondly, it can be seen that its corrosion current density is 2.35×10 -5 A / cm 2 The current density is inversely proportional to the corrosion rate. A smaller current density indicates that the steel has excellent corrosion resistance.

[0052] Example 3

[0053] A method for preparing a biodegradable antibacterial magnesium alloy staple comprises the following steps:

[0054] S1. Weigh 150g of metallic calcium, 60g of metallic zinc and 790g of metallic magnesium, all with a purity of 99.99%; melt the magnesium block in a resistance furnace in a mixed atmosphere of SF6 and CO2 (wherein SF6 accounts for 1 vol.%), heat it to 650°C, keep it warm for 3h, preheat the metallic calcium and other raw materials and slowly add them into the magnesium liquid in batches; refine the mixed magnesium liquid; after refining, put it back into the resistance furnace, heat it to 1100°C, keep it warm for 30min, pour it, and obtain a magnesium ingot Mg-15Ca-6Zn after cooling; anneal the magnesium ingot at 800°C, and then perform multi-pass hot drawing at 400°C, draw it to 0.2mm, obtain a magnesium alloy wire, rinse it with deionized water and dry it;

[0055] S2, immersing the prepared magnesium alloy wire into a silane coupling agent for functionalization;

[0056] S3. Weigh 10g of black phosphorus, grind it into powder, disperse it in 2ml of N-methylpyrrolidone, ultrasonicate it in an ice bath for 10h, and then centrifuge it at high speed to obtain a black phosphorus solution with a concentration of 5g / ml; weigh 10g of cellulose, dissolve it in 1ml of dimethyl sulfoxide, stir it at room temperature for 2h, and obtain a uniform solution with a concentration of 10g / ml; stir and mix the black phosphorus solution and the cellulose solution at 38°C for 24h to obtain a mixed coating solution with a mass ratio of 10:1;

[0057] S3. The wire obtained in S1 was immersed in the solution of S2 for 30 minutes by an immersion method, the coating solution obtained in S2 was coated on the surface of the wire obtained in S1, and the wire was irradiated and cured under ultraviolet light for 14 hours to obtain a biodegradable antibacterial magnesium alloy staple.

[0058] After the metal is corroded, some physical and mechanical properties of the metal will change to a certain extent, such as mass, thickness, mechanical properties, organizational structure, resistance, etc., which may change. Therefore, the changes in these physical properties of the metal can be used to represent the corrosion rate of the metal. As shown in Table 1, the annual corrosion rate of Mg-15Ca-6Zn before and after coating, the depth index of the corrosion rate is used, that is, the thickness of the metal sample corroded in a year per unit time. The smaller the corrosion rate value, the stronger the corrosion resistance. It can be seen that the corrosion rate after coating is much lower than the corrosion rate of the sample before coating, so it can be obtained that the corrosion resistance after coating is greatly improved.

[0059] Table 1

[0060] sample Annual corrosion rate (mm / y) Mg-15Ca-6Zn uncoated ~1.63 After Mg-15Ca-6Zn coating ~0.87

[0061] The above is only an exemplary embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present disclosure should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A biodegradable antibacterial magnesium alloy staple, characterized in that: The magnesium alloy staple comprises Mg-xCa-yM wire, biopolysaccharide and its derivatives and black phosphorus mixed coating, wherein M in the Mg-xCa-yM wire is Mn and Y, the mass fraction of x is 0.1%-15%, and the mass fraction of y is 0.01%-6%; The method for preparing the magnesium alloy anastomotic staple comprises the following steps: S1. Weigh the required raw materials of calcium metal, manganese metal, yttrium metal and magnesium metal, melt the magnesium metal block in a resistance furnace in a mixed atmosphere of SF6 and CO2, heat it to 650-780°C, and keep it warm for 1.5-3h to obtain magnesium liquid, preheat the calcium metal, manganese metal and yttrium metal, and then slowly add them into the magnesium liquid in batches, refine the mixed magnesium liquid, put it back into the resistance furnace for heating after refining, pour it, and obtain a magnesium ingot after cooling, anneal the magnesium ingot and then perform hot drawing to obtain a magnesium alloy wire; S2, immersing the magnesium alloy wire in a silane coupling agent for functionalization; S3, weighing the required black phosphorus, grinding it into powder, dispersing it in N-methylpyrrolidone, ultrasonicating it in an ice bath for 10 hours, and then high-speed centrifuging it to obtain a black phosphorus nanosheet solution, weighing the required biopolysaccharides and their derivatives, dissolving them in an organic solvent, stirring them at room temperature for 2 hours to obtain a uniform polysaccharide solution, and stirring and mixing the black phosphorus nanosheet solution and the uniform polysaccharide solution at 36-38° C. for 12-24 hours to obtain a mixed coating solution of black phosphorus and biopolysaccharides and their derivatives; S4, coating the coating solution prepared in S3 on the surface of the functionalized wire prepared in S2 by dipping, spraying or hydrothermal synthesis, and curing under ultraviolet light for 10-14 hours to obtain a biodegradable antibacterial magnesium alloy staple with a coating thickness of 0.1-200 μm; In S3, the concentration of the black phosphorus nanosheet solution is 0.1-5 g / ml, the molecular weight of the biopolysaccharide and its derivatives is 2000-50000 Da, the concentration of the uniform polysaccharide solution is 0.5-10 g / ml, and the mass ratio of the black phosphorus to the biopolysaccharide and its derivatives in the mixed coating solution is 0.005:1-10:1; In S3, the biopolysaccharide and its derivatives are one or more of alginate, chitosan, chitosan polyammonium salt, dandelion polysaccharide, dextran, astragalus polysaccharide, polygonatum polysaccharide, rehmannia polysaccharide, chitin, cellulose, hyaluronic acid, chondroitin sulfate, and heparin.

2. The biodegradable antibacterial magnesium alloy staple according to claim 1, characterized in that: In S1, after refining, the steel is put back into the resistance furnace, heated to 800-1100° C., and kept warm for 30-60 minutes.

3. The biodegradable antibacterial magnesium alloy staple according to claim 1, characterized in that: In S1, the magnesium ingot is annealed at 400-800°C, and then hot drawn at 200-400°C for multiple passes, and the magnesium alloy wire is drawn to 0.2-0.6 mm.

4. The biodegradable antibacterial magnesium alloy staple according to claim 1, characterized in that: In S1, the purity of the raw materials is 99.99%, and in the mixed atmosphere of SF6 and CO2, the volume ratio of SF6 to CO2 is 90-100:

1.

5. The biodegradable antibacterial magnesium alloy staple according to claim 1, characterized in that: In S3, the organic solvent is one of N,N-dimethylformamide, tetrahydrofuran, ethanol, acetone, isopropanol, dimethyl sulfoxide, N-methylpyrrolidone, pyridine, and acetonitrile.

6. The biodegradable antibacterial magnesium alloy staple according to claim 1, characterized in that: In S4, the immersion time is 5-30 min, the spray carrier gas is one of nitrogen and argon, the gas pressure is 0.5-0.9 MPa, the spray distance is 10-50 mm, the nozzle movement speed is 10-30 mm / s, the hydrothermal synthesis temperature is 120-200° C., and the time is 12-24 h.